Intervensi Terapi Spherical Grip dalam Upaya Melatih Gerak ROM Ekstermitas Atas untuk Meningkatkan Kekuatan Otot pada Pasien Stroke - Lia Astuti (Journal of Nursing Perspectives, 2025)
Background: Stroke is one of the leading causes of disability worldwide and significantly affects physical mobility. This study aimed to describe the application of spherical grip therapy in improving upper extremity muscle strength in stroke patients. Methods: A descriptive case study design was used involving one patient diagnosed with stroke and impaired upper extremity mobility. The intervention was spherical grip therapy conducted for 10–15 minutes once daily for six consecutive days. Muscle strength was measured using a standardized muscle strength grading scale before and after the intervention. Results: Before the intervention, the patient’s muscle strength in both upper extremities was scored at 3 (movement against gravity only). After six therapy sessions, muscle strength improved to 4 (movement against gravity with minimal resistance). The patient also reported reduced stiffness and improved relaxation during daily activities. Conclusion: Spherical grip therapy is effective as a non-pharmacological nursing intervention to enhance upper extremity strength and mobility in stroke patients. This therapy may be recommended as part of nursing care interventions to support stroke rehabilitation programs.